Pengaruh Latihan Kekuatan Otot Lengan Terhadap Kemampuan Passing Atas Bola voli - Faisal, Muhamad Ikhsan; Arifin, Z; Permadi, Asep Angga (Jurnal Porkes, 2025)
This study aims to analyze the effect of arm muscle strength training on upper passing ability in volleyball games. The research method used an experiment with a pretest-posttest design. The research sample was 15 male volleyball extracurricular students at SMAN 13 Garut using total sampling technique. The research instrument was a test and measurement of upper passing ability, with criterion validity based on predetermined standards. The results showed that there was an increase in the average upper passing score from the pretest of 40.93 to 50.07 in the posttest, with a difference of 9.14. In addition, the statistical test results showed a significance value (sig. 2-tailed) of 0.000, which is smaller than the significance level of 0.05, indicating a significant difference between the pretest and posttest results. These findings suggest that arm muscle strength training contributes to improving upper passing skills by improving players' propulsion and movement stability. This study provides important implications for volleyball coaches and extracurricular coaches in designing more effective and evidence-based training programs to improve player performance. Thus, arm muscle strength training can be used as one of the recommended training methods to improve the quality of the upper passing technique in volleyball games.